Relationship of Primary Nurses Service with Satisfaction of Patients of Road Poli Care in Kudungga District of Eastern Kutai - Yayuk Widyanti; Hilda Hilda; Arsyawina Arsyawina (International Journal of Global Sustainable Research, 2023)
Patient satisfaction rate data on primary poli street care services in RSUD Kudungga 2023 has not been re-enquiried by the hospital.The study aims to explain the relationship between primary nurses' services and the satisfaction rate of road polio patients in Kudungga district of Eastern Kutai district in 2023. Type of quantitative research with analytical studies and using cross sectional designs.The sample was 186 people using purposive sampling. The instrument used is a questionnaire.The data was then analyzed univariately and bivariately with the Chi Square test. The results of the research showed that there was a relationship between primary nursing services and the satisfaction rate of the patients of the RSUD Kudungga medical clinic.